OPTIMALISASI LITERASI DAN NUMERASI MELALUI PENDAMPINGAN BELAJAR BERBASIS LINGKUNGAN PADA SISWA KELAS III SDN 077/VII TAMBANG TINGGI - Saskia, Arna; Raja Novriadi; Aulia Intan Sari; Irman Maulana; Linda Sukma Sari; Nadiatul Silmi; Serli Nor Sinta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of environmental-based learning assistance and its contribution to strengthening literacy and numeracy skills among third-grade students of SDN 077/VII Tambang Tinggi. The study was adapted from a research-based community service report and written in the format of a scientific article. A descriptive qualitative approach was used with 10 students as research subjects. Data were collected through observation, interviews with the class teacher and students, and documentation during 40 days of assistance activities. Data were analyzed through data reduction, data display, and conclusion drawing. The findings show that the assistance was carried out in stages, beginning with an initial mapping of students’ abilities, followed by contextual literacy and numeracy activities using concrete objects from the surrounding environment. The program created a more active, enjoyable, and meaningful learning atmosphere. Students showed better reading fluency, increased confidence in reading aloud, improved simple writing, and stronger understanding of addition and subtraction through real objects such as stones, leaves, and sticks. Environmental-based learning assistance also increased learning motivation and student participation. The study concludes that simple environmental resources can function as effective learning media for strengthening elementary students’ literacy and numeracy.